Política institucional de inovação : um panorama da Universidade do Estado de Mato Grosso (UNEMAT) - Rosa, Claudia Marisa (2020)
In the last two decades, the incentive to innovation has guided the public policies of science and technology in the country to the point of configuring, for the area, the trinomial science, technology and innovation (CT&I). Policies in this area resulted in the implementation of financing mechanisms, action plans, reconfiguration of institutional structures and, above all, in the creation of Law no. 10.973 of december 2, 2004, called the Innovation Law, aiming at the legal security of the innovation process. In this scenario, the importance of ICTs in the development process based on CT&I was highlighted. With the reformulation of the Innovation Law by Law no. 13.243 of January 11, 2016, called the CT&I Legal Framework, it became mandatory for public ICTs to institute an innovation policy with guidelines on the organization and management of processes that guide the transfer of technology and the generation of innovation. In this context, the general objective of this study was to analyze the innovation policy of the State University of Mato Grosso (UNEMAT), aiming to identify the mechanisms of incentive to innovation that the institution has in its institutional guidelines, considering the reformulation of such guidelines that occurred recently. To this end, we sought to identify the institutional landscape of the teaching, research and extension tripod to understand the basis for the development of innovation in the institution, and then prepare a technical report for the analysis of the institutional innovation policy. The study is characterized by applied research with a qualitative approach from bibliographic and documentary sources, using a combination of qualitative analysis methods, participant observation and data triangulation for its elaboration. The results of the study, regarding the institutional panorama, demonstrate a very young university, but consolidated in teaching, research and extension, and, under development in the scope of innovation, with indicators still inexpressive, despite the identified innovation potential. Regarding the mechanisms of incentive to innovation, the study points out that with the reformulation of the innovation policy, a series of mechanisms were institutionalized to encourage and give legal certainty to the innovation process, such as scholarships, removal, exercise of pertinent paid activity innovation, participation in the gains resulting from innovation, infrastructure sharing, execution of strategic partnerships, internationalization aiming at innovation, among others. With this, it is possible to conclude that the institution evolves considerably in terms of institutional innovation policy, which represents an important initial step. However, it is necessary to monitor and evaluate this policy to ensure the effectiveness of the institutionalized mechanisms, so that the institution will leverage its indicators and also consolidate itself in the scope of innovation.